2019
DOI: 10.1038/s41598-019-51612-z
|View full text |Cite
|
Sign up to set email alerts
|

Tracking genome-editing and associated molecular perturbations by SWATH mass spectrometry

Abstract: Advances in gene editing now allow reverse genetics to be applied to a broad range of biological systems. Ultimately, any modification to coding sequences requires confirmation at the protein level, although immunoblotting is often hampered by antibody quality or availability especially in non-model species. Sequential Window Acquisition of All Theoretical Spectra (SWATH), a mass spectrometry (MS) technology with exceptional quantitative reproducibility and accuracy, offers an ideal alternative for protein-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Unfortunately, we were not able to test this as there are currently no antibodies that uniquely recognize Hmx3a and we would require an antibody that recognizes the N-terminal region of Hmx3a that should be conserved in our single mutant Hmx3a proteins. In addition, we were unable to detect any Hmx3a peptides in a SWATH analysis (data not shown; Hmx3a has also not been detected in other SWATH analyses; Blattmann et al 2019 ; Lin et al 2019 ), presumably because, like many transcription factors, it is expressed in either two few cells and/or at too low a level.…”
Section: Discussionmentioning
confidence: 79%
“…Unfortunately, we were not able to test this as there are currently no antibodies that uniquely recognize Hmx3a and we would require an antibody that recognizes the N-terminal region of Hmx3a that should be conserved in our single mutant Hmx3a proteins. In addition, we were unable to detect any Hmx3a peptides in a SWATH analysis (data not shown; Hmx3a has also not been detected in other SWATH analyses; Blattmann et al 2019 ; Lin et al 2019 ), presumably because, like many transcription factors, it is expressed in either two few cells and/or at too low a level.…”
Section: Discussionmentioning
confidence: 79%
“…To demonstrate that, as with other phenotypes, the H 2 O 2 increase in hai1a was due to unrestrained activity of Matriptase1a, we used a matriptase1a mutant allele, st14a sq10 , which prematurely terminates the protein at 156 amino acids ( Figure 2A , Figure 2—figure supplement 1A–C ; Lin et al, 2019 ). Zygotic st14a mutants showed no overt phenotype; however, maternal zygotic mutants lacked ear otoliths ( Figure 2B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…The hai1a/ddf alleles used were hai1a hi2217 , hai1a fr26 , ddf ti251 , and ddf t419 . The st14a sq10 allele was generated previously ( Lin et al, 2019 ). For imaging neutrophils and keratinocytes, the transgenic lines Tg(mpx:EGFP) i114 ( Renshaw et al, 2006 ) and Tg(krtt1c19e:lyn-tdtomato) sq16 ( Lee et al, 2014 ) were used, whilst early leukocytes were imaged with Tg(fli1:EGFP) y1 ( Redd et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of CD81 partially rescued the infertility phenotype seen in CD9 KO mice [ 39 ] and it was recently demonstrated that CD9 deletion in human melanoma cells was quickly compensated by CD63 expression upregulation [ 40 ]. It would be interesting to perform RNA-seq or SWATH-MS on the cd9 dKOs to identify upregulated RNA and proteins respectively [ 41 ].…”
Section: Discussionmentioning
confidence: 99%